2014
DOI: 10.1093/cjres/rsu029
|View full text |Cite
|
Sign up to set email alerts
|

Recessions, recoveries and regional resilience: evidence on Italy

Abstract: This paper analyses regional resilience and local economic growth patterns in Italy over the past four decades. Place-specific transient and permanent effects of aggregate employment shocks are studied. Geographical asymmetries in engineering and ecological resilience are found, providing auxiliary insights on the rooted Italian regional inequalities. The territorial impact of different crises is investigated and a direct comparison with the UK case is offered. The importance of manufacturing activities for ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(98 citation statements)
references
References 35 publications
4
77
1
5
Order By: Relevance
“…income and employment. Indeed, as mentioned earlier in this paper, the results obtained by both Cellini and Torrisi (2014) and Di Caro (2014a) seem to affirm the existence of differences in impact and/or recovery coefficients, potentially interpretable on a geographical basis. To explore this issue, we consider Moran's I index of spatial correlation (Moran, 1948).…”
Section: Insert About Heresupporting
confidence: 84%
See 3 more Smart Citations
“…income and employment. Indeed, as mentioned earlier in this paper, the results obtained by both Cellini and Torrisi (2014) and Di Caro (2014a) seem to affirm the existence of differences in impact and/or recovery coefficients, potentially interpretable on a geographical basis. To explore this issue, we consider Moran's I index of spatial correlation (Moran, 1948).…”
Section: Insert About Heresupporting
confidence: 84%
“…The adverse common shocks hitting the regions are, in substantial terms, three (Bassanetti et al, 2010) Here we provide a description of regional reactions to such shocks, basing on two recent analyses that take the resilience analysis perspective: Cellini and Torrisi (2014) and Di Caro (2014a However, as yet pointed out in a pioneering contribution of Blanchard and Katz (1992) on regional evolution in the US, the place-specific response of regional and local labour markets to national adverse events -either economic recessions or other unexpected disturbances-can result in a multifaceted set of outcomes and adjustment mechanisms.…”
Section: Regional Resilience In Italy: Evidence From Income Vs Emplomentioning
confidence: 99%
See 2 more Smart Citations
“…Martin et al argued that regionally-specific factors can predict the ability of a region to resist and respond to economic shocks [13]. Lagravinese suggested that regions with a higher share of public and service industries are more resistant to economic shocks [37], while Di Caro found that certain types of manufacturing activities could help to explain the high resilience of some regions during recessions and recoveries [14]. Pike examined the role of local institutions and governance in shaping regional resilience [38].…”
Section: Determinants Of Regional Resiliencementioning
confidence: 99%